Photophysical and electrochemical properties of two trans-A2B-corroles: differences between phenyl or pyrenyl groups at the meso-10 position. Issue 29 (16th July 2020) - Acunha, Thiago V.; Victória, Henrique F. V.; Krambrock, Klaus; Marques, Amanda C.; Costa, Luiz Antônio S.; Iglesias, Bernardo A.
Abstract : The photophysical properties of two meso–trans -A2 B-type corroles containing phenyl or pyrenyl units were reported in this study. TD-DFT calculations and electrochemical analysis were conducted to better understand the corrole molecular structures. Abstract : The present study reports on the optical and photophysical properties of trans -A2 B-corroles possessing pyrenyl units attached at the meso -10-position and compares them with those of model trans -A2 B-corroles having phenyl substituents at that position. In contrast to the model meso -substituted corrole, the new pyrenyl-corrole shows slightly red-shifted absorption bands and blue-shifted emission, slightly higher fluorescence quantum yield, and more importantly, it shows better photo-stability under white-light illumination. Theoretical calculations were used to determine the electronic transitions and geometries of the singlet and triplet excited states (TD-DFT and NTO). Moreover, we demonstrate that the pyrenyl-corrole in analogy to previously studied model corroles is able to generate reactive oxygen species (ROS) under visible light using photo-degradation of 1, 3-diphenylisobenzofuran (DBPF), a singlet oxygen quencher, and EPR spectroscopy allied with the spin-trapping method is used for identifying singlet oxygen species. The results show that the pyrenyl unit attached at the meso -10-position of the corrole increases the photo-stability and efficiency in ROS generation compared to the phenyl substituent.